La aplicación lúdica “el juego de la ortografía” como herramienta para mejorar las habilidades ortográficas en los estudiantes de décimo año de educación general básica, paralelo “b” en la “Unidad Educativa Roberto Alfredo Arregui Chauvin” en la provincia bolívar, cantón Guaranda en el periodo lectivo 2022 2023 - Chileno Quillay, Jefferson Rodrigo (2023)
The present investigation entitled "The playful application "the spelling game" as a tool to improve spelling skills in tenth-year students of Basic General Education, parallel "B" in the Educational Unit “Roberto Alfredo Arregui Chauvin" in the Bolívar province, Guaranda canton in the 2022-2023 school period", because students have spelling problems and teachers do not have a didactic guide to solve these problems. Consequently, students are prone to continue committing those problems that will affect them in their future. The primary objective of this project is to propose a didactic guide for the playful application "the spelling game" to improve students' spelling skills. In scientific theory, a large amount of information is addressed based on the subject matter. And, the methodology that was used was quantitative because it provided us with quantitative data. Regarding the analysis and interpretation of results, characteristic results were obtained in relation to the problem and the objectives of this research project, they were of great help to determine that the students of the tenth year of Basic General Education, parallel "B" of the Educational Unit “Roberto Alfredo Arregui Chauvin" present problems in terms of spelling rules.